Analysis of Financial Distress Using Altman Methode (Z-score) in Bank Umum Milik Negara (BUMN) - Empon Tri Ayu; Ida Anggriani; Herlin Herlin (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study was to analyze bankruptcy using the Altman (Z-Score) method at State-Owned Commercial Banks (BUMN). The results showed that PT. BRI (Persero) Tbk with a condition that is not bankrupt or healthy in 2015 and 2016 the Z-score is 3,404 and 3,341. In 2017 the Z-score is 2,099, in 2018 it is 1,901 and in 2019 it is 2,057 which means it is included in the gray area (it is in growth zone). PT. BNI 46 (Persero) Tbk in 2015 obtained a Z-score of 4.213, meaning that it is not in a state of bankruptcy or health. In 2016 the Z-score was 1.622, 2017 was 1.702, in 2018 it was 1.578 and in 2019 it was 1.388, this means it is included in the gray area (in the growth zone). PT. Bank Mandiri (Persero) Tbk, in 2015 obtained a Z-score of 1,985, in 2016 was 2,074, in 2017 it was 1,914, in 2018 it was 1,818 and in 2019 it was 1,943, this means it is included in a gray area or in a growth zone. PT. BTN (Persero) Tbk in 2015 obtained a Z-score of 1.659, meaning it is included in the gray area (in the growth zone). In 2016 the Z-score was 0.932, 2017 was 0.962, 2018 was 0.835 and 2019 is 0.912, this shows that PT. BTN (Persero) Tbk has the potential to go bankrupt.